FEATURES OF CORRELATIONSHIP AMONG QUANTITATIVE TRAITS IN SOYBEAN BREEDING ACCESSIONS - D. R. Shaphigullin; E. V. Romanova; M. S. Gins; V. K. Gins; E. P. Pronina (Овощи России, 2017)
The main problem of agroindustrial sector of national economy is an absence of sufficient production of plant proteins that are used for food production as well as a forage production. New cultivars of  legumes, namely in  soybean have to  be developed to resolve this task. Soybean seeds contain much protein up to 50%, fat up to 28 %, along with  vitamins, phospholipids,  isoflavones and ferments. Soybean is a short-day crop. The main reason that limits the spread of soybean is the absence of new early-ripening cultivars. Folk cultivars and varieties native to China produce the grain yield at the sum of temperatures over 3500oC. At the beginning of the last century, there were bred the varieties that  produced  the grains at the sum of temperatures  below  3000oC.  Only after  that  the soybean as a crop is started to be introduced in different countries. The study on association among quantitative traits is needed to select necessary accessions for breeding program. In this research estimation of correlationship based on data of structure analysis was carried out within two-year period.  The correlationship  of  economically valuable traits, such as 1000 seed grain weight, number of grains in bean (pod) and other traits such as plant height, stem thickness, the height of pod  attachment, a number of branches, number of pods on the plant, number of productive nodes, average number of pods at node, average number of grains (beans) per plant in field experiment in 2015-2016, Central Zone of Non-chernozem Zone of Russia. It was noticed  the difference in trait correlationship depended on a year, and it needs to be taken into account for realization of breeding program in soybean.